Molecular identification of Flavobacterium psychrophilum and characterization of cutaneous alterations in rainbow trout (Oncorhynchus mikyss) from Puno, Peru - Távara P., Carlos (2020)
The aim of this study was to compare histological lesions of rainbow trout (Oncorhynchus mikyss) affected by the bacterial cold water disease (BCDW) with asymptomatic trout skin samples from fish farms in Lake Titicaca (Puno, Peru) and identify the presence of Flavobacterium psychrophilum by conventional PCR. Thirteen trout with skin lesions and seven without lesions, with sizes greater than 25 cm and average weight of 350 g were used. Conventional PCR was performed for the identification of Flavobacterium psychrophilum, using primers directed to the 16S rRNA region. Molecularly, both groups of animals were positive for the presence of F. psycrophilum. It can be concluded that this pathogen is present in the southern part of the country.